Seeing the talker’s face supports executive processing of speech in steady state noise - Mishra, Sushmit; Lunner, Thomas; Stenfelt, Stefan; Rönnberg, Jerker; Rudner, Mary (Frontiers in Systems Neuroscience, 2013)
Listening to speech in noise depletes cognitive resources, affecting speech processing. The present study investigated how remaining resources or cognitive spare capacity (CSC) can be deployed by young adults with normal hearing. We administered a test of CSC (CSCT, Mishra et al., 2013) along with a battery of established cognitive tests to 20 participants with normal hearing. In the CSCT, lists of two-digit numbers were presented with and without visual cues in quiet, as well as in steady-state and speech-like noise at a high intelligibility level. In low load conditions, two numbers were recalled according to instructions inducing executive processing (updating, inhibition) and in high load conditions the participants were additionally instructed to recall one extra number, which was the always the first item in the list. In line with previous findings, results showed that CSC was sensitive to memory load and executive function but generally not related to working memory capacity. Furthermore, CSCT scores in quiet were lowered by visual cues, probably due to distraction. In steady-state noise, the presence of visual cues improved CSCT scores, probably by enabling better encoding. Contrary to our expectation, CSCT performance was disrupted more in steady-state than speech-like noise, although only without visual cues, possibly because selective attention could be used to ignore the speech-like background and provide an enriched representation of target items in working memory similar to that obtained in quiet. This interpretation is supported by a consistent association between CSCT scores and updating skills.